The Greek Genocide and Smyrna’s Catastrophe: An Overview - Malkidis, Theofanis S. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Genocide is a crime against humanity which should be universally condemned. Regardless of the time that passes or the scope of the crime itself, there should be no reduction of the importance of a crime against humanity or the responsibility of those who commit genocide. The 20th century is, without a doubt, an era where the crime of genocide appeared and reappeared consistently. The Armenian, Greek, and Assyrian Genocide and the Holocaust, constituted important genocides perpetrated by illiberal governments that violated numerous human rights, taking millions of lives and eliminating the history and civilization of cities dating backthousands of years. From World War II onwards, “genocide” was coined as a criminal form of behaviour that constitutes one of the most violent crimes one could be charged with. The Greek Genocide, one of the first genocides of the 20th century, is one of the big crimes against humanity that remains unpunished to this day since a large part of a nation that lived on the territory of the Ottoman Empire was murdered. The Smyrna Catastrophe of 1922 constituted the symbolic end of the Greek Genocide.
Keywords: Ottoman Empire; Genocide